Characterization of Residual Carbon in Fly Ashes from Power Plants Firing Biomass - Zhao, M.; Han, Z.; Sheng, C.; Wu, Hongwei (American Chemical Society, 2013)
Fly ash samples were collected from grate fired power plant units burning mixed fuels of agricultural residues and woody biomass. The fly ashes were characterized in terms of the residual carbon mainly via nonisothermal thermogravimetric analysis (TGA) technique and loss-on-ignition (LOI) approach. TGA by heating of the fly ashes at 7 °C/min to 900 °C in air atmosphere showed three distinct peaks of weight loss in the temperature ranges of 350-530 °C, 530-660 °C, and 660-900 °C, which were confirmed to result mainly from the oxidation of residual carbon, the decomposition of calcium carbonate, and the release of alkali chlorides related species, respectively. It was shown that nonisothermal air TGA can distinguish the contribution of residual carbon oxidation to weight loss from those of the reactions of inorganic matter and, therefore, can be used as a simple technique for estimating the residual carbon content in biomass combustion fly ashes for engineering applications. The residual carbon content determined by TGA was compared with that from LOI measurements at 450 and 550 °C. The size distribution of the residual carbon in the fly ashes and the combustion reactivity of the residual carbon in large size fractions (>200 µm) of these fly ashes were also investigated, aiming at exploring the recovery and application of the residual carbon.